1994
DOI: 10.1021/tx00038a008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peroxidase-Catalyzed Reactions by Arylamines: Mechanism for the Anti-Thyroid Action of Sulfamethazine

Abstract: Sulfonamide antibiotics, typified by sulfamethazine (SMZ), are widely used in veterinary practice. Sulfonamide residues in milk and meat products are of regulatory concern since SMZ is a thyroid carcinogen in rodents and sulfonamide-induced hypersensitivity reactions, including hypothyroidism, have been reported in humans. SMZ and other primary arylamines inhibited iodination reactions catalyzed by thyroid peroxidase (TPO) and the closely related lactoperoxidase (LPO). Inhibition of LPO-catalyzed triiodide ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The mammalian peroxidases including LPO are also involved in catalyzing the single electron oxidation of various physiologically important organic aromatic substrates including phenols (23,24), catecholamines, and catechols (25)(26)(27) as well as other experimental model compounds such as aromatic amines (28), polychlorinated biphenyls (29), steroid hormones (30 -32), and polycyclic aromatic hydrocarbons (33). However, the mode of binding of aromatic ligands and associated functional implications are not yet clearly understood.…”
Section: Lactoperoxidase (Lpo)mentioning
confidence: 99%
“…The mammalian peroxidases including LPO are also involved in catalyzing the single electron oxidation of various physiologically important organic aromatic substrates including phenols (23,24), catecholamines, and catechols (25)(26)(27) as well as other experimental model compounds such as aromatic amines (28), polychlorinated biphenyls (29), steroid hormones (30 -32), and polycyclic aromatic hydrocarbons (33). However, the mode of binding of aromatic ligands and associated functional implications are not yet clearly understood.…”
Section: Lactoperoxidase (Lpo)mentioning
confidence: 99%
“…The first step is iodination of thyroglobulin tyrosyl residues, followed by oxidative coupling to yield T 4 and T 3 . Inhibition of porcine TPO activity is a mechanism common to many classes of synthetic antithyroid compounds (27)(28)(29)(30)(31) and naturally occurring flavonoids (32,33). Lactoperoxidase (LPO) is often used as a model for TPO, based on many shared structural and functional properties.…”
Section: Biosynthesis Of Thyroid Hormones and Inhibition By Antithyromentioning
confidence: 99%
“…It has also been shown that ascorbic acid, cysteine, epinephrine, norepinephrine, serotonin, NADH, and NADPH can inhibit tyrosine iodination (13). More recent studies have shown that some exogenous substances such as dietary flavonoids and sulfamethazine may impair TPO activity, at least in vitro (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by this author, since the oxidized form of iodide might act to oxidize the thioureylene drugs, as well as to iodinate tyrosine residues, the thioureylenes may compete with the tyrosyl residues for the oxidized iodide and so inhibit the iodination reaction. Some authors have also demonstrated that several mechanisms can be responsible for the inhibition of TPO-and LPO-catalyzed reactions, such as suicide inactivation of the enzyme, rapid equilibrium binding, and alternate substrate competition for the iodinating intermediate (15).…”
Section: Discussionmentioning
confidence: 99%